Economic Growth, humand capital and negative externalities: stability and chaos - London, Silvia (2009)
In this work we analyze the importance of the accumulation of human capital through the formal educational system for economic growth. We base our analysis on two previous models (London: 2005, London: 2006) in which, starting with the framework in (Lucas: 1988) we add a parameter of distortion on the formal educational sector. The mathematical model is built upon a logistic equation. Since it is not analytically solvable, we run simulations for different scenarios, using data from Argentina. The main conclusion we reach is that the stability of the growth process depends critically on afine tuned combination of the main variables. This suggests very specific policies of development that albeit being intuitively sound, can be inefficient.